Doing business with criminals: between exclusion and surveillance - Moiseienko, Anton (Cambridge University Press, 2025)
"This book explains why we have anti-money laundering, counter-terrorist financing and sanctions laws, and how they can work better. It provides a historically informed and balanced account of how those rules have emerged and what they mean in practice for governments, law enforcement agencies and private businesses"-- Provided by publisher